GAMBARAN POLA MENYUSUI DAN PERTAMBAHAN BERAT BADAN BAYI 0-6 BULAN PADA KELUARGA PEROKOK DAN TIDAK PEROKOK DI KOTA BINJAI TAHUN 2016 - Irfan .; Etti Sudaryati; Ernawati Nasution (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
Breastfeeding period is a very important and valuable period for a mother and her baby. During breastfeeding period, most of the nutritional needs of infants derived from breastmilk, therefore the consumption of infants calories and nutritions during breastfeeding was influenced by the quality and quantity of breast milk consumed by the baby. This study aimed to determine the breastfeeding pattern and the 0-6 months baby weight gain in smoker and non-smoker families in Binjai. This study was descriptive with cross sectional design and the sample size of 100 infants aged 0-6 months, with gradual clustering technique. Data were collected based on study variables of the breastfeeding pattern, baby weight gain, family smoking status, with direct interviews of respondents (mothers) using closed questionnaires. The results showed that 100 infants 0-6 months were from 46% of smoker families and 54% of non-smoker families. Among the 46% of smoker families, families that have infants with good breastfeeding pattern were 76.1% and infants with good weight gain were 56.5%. Among the 54% of non-smoker families, infants with good breastfeeding patterns were 61.1% and infants with good weight gain were 75.9%.It was expected to provide input to the Community Health Center to increase public knowledge through counseling about the hazard of cigarette smoke that gives effect to breastfeeding mothers and baby weight gain. To non-smoker families was suggest to reduce the number of daily cigarettes smoked and not smoking in the house especially near the baby. Keywords: Breastfeeding Pattern, Baby Weight Gain, Smoker and Non-smoker Family